Countering Social Stigma as the Basis of Interfaith Movement: A Case Study of Cadar Garis Lucu - Andi Alfian; Wahyuddin Halim (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2022)
One of the weaknesses of interfaith dialogue in Indonesia is the lack of participation and space for women’s voices. Almost all spaces for interfaith dialogue are dominated by men, even though women have an important role in interfaith dialogue. Therefore, we should involve more women than men, not only because women are the most affected when religious conflicts occur but previous studies have also shown that women are most effective in peacebuilding negotiation based on non-violent strategies. This study investigates an interfaith movement, Cadar Garis Lucu, which veiled/niqab women initiated to counter the stigma that veiled/niqab women are radical-extremist and anti-other religions. Besides being active in promoting peace and interfaith dialogue, Cadar Garis Lucu also promotes the discourse of gender equality. By employing qualitative research and in-depth interview method as the primary data collection technique, this study found that Cadar Garis Lucu is an interfaith movement that aims to counter society’s negative stigma towards women – both veiled/niqab women and women in general – and seeks to bring women to participate in interfaith dialogue. Furthermore, this study argues that there is no better way to peacebuilding than to give space for women in interfaith dialogue.